An Empirical Examination of the Multi-dimensionality of Ethical Climate in Organizations - Wimbush, James C. (Journal of business ethics, 1997)
The purpose of this study was to determine whether the ethical climate dimensions identified by Victor and Cullen (1987, 1988) could be replicated in the subunits of a multi-unit organization and if so, were the dimensions associated with particular types of operating units. We identified three of the dimensions of ethical climate found by Victor and Cullen and also found a new dimension of ethical climate related to service. Partial support was found for Victor and Cullen's hypothesis that certain ethical climate dimensions are associated with particular forms of organizational governance and control.